Penempatan, Pengembangan Karier dan Kesejahteraan Karyawan di MA PP Darussalam Kasomalang - Muhamad Badar Badrudin; Wahyu Hidayat (Journal on Education, 2024)
This study aims to analyse the practices of placement, career development and employee welfare at MA PP Darussalam Kasomalang, and to examine their impact on work effectiveness and the quality of the organisational environment. Using a qualitative approach with a case study method, this research involved educators, administrative staff, and management as research subjects. Data were obtained through in-depth interviews, direct observation, and document analysis, then analysed thematically to identify relevant patterns. The results showed that employee placement based on a match between individual competencies and organisational needs contributed to increased productivity and job satisfaction. The career development programme implemented, although still limited, is able to encourage employee motivation and loyalty. Meanwhile, employee well-being, which includes physical, psychological and work-life balance aspects, plays an important role in maintaining retention and creating a harmonious working environment. The relationship between placement, career development and employee welfare proved significant in supporting the achievement of the institution's overall goals. This research makes a practical contribution to human resource management in educational institutions by recommending more structured strategies in employee placement, provision of comprehensive career development programmes, and improved welfare policies.